Effect of organic & biofertilizer on the growth of patchouli plant (Pogostemon cablin) - Ahmad Farhan, Md. Shokeri (2008)
Patchouli was first described by botanists in the Philippines in 1845. Today growing interest in its fragrance has led to patchouli's widespread cultivation throughout tropical Asia. The research is focused on the growth of patchouli plant (Pogostemon cablin) and its essential oil production. The objective of this research is to study the effect of organic and biofertilizer on the growth of patchouli plant (Pogostemon cablin). All the fertilizer that was used in this research was analyzed to determine it characteristic using DR 2800 Spectrophotometer (HATCH) and Polarized Zeeman Atomic Absorption Spectroscopy (HITACHI). There were 28 patchouli plants was used in this research and hydro distillation was proposed to extract it essential oil. Patchouli oil accounted for about 2-3% of the patchouli dried leaves. The growth of plant had no significant affected by types of fertilizer. However the highest yield of oil was observed at 1.231 g/g using biofertilizer, which is 155% increase compared to control. -Author